Impact of climate change and human activities on the sustainable development of Xinjiang Aksu Oasis (China) - Duan Zhengrong; Ni Mingxia; Tao Ya; Marcin Sobota; Xia Jianxin (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: To show that the Oasis in Xinjiang of China is facing serious sustainable development challenges due to the climate change and human activities, especially for the drought stress.